Confocal microscopy as an early relapse marker for acanthamoeba keratitis. Issue 1 (27th July 2017) - Daas, Loay; Viestenz, Arne; Schnabel, Philipp Albert; Fries, Fabian N.; Hager, Tobias; SzentmÁry, Nora; Seitz, Berthold
Abstract : Acanthameoba keratitis is a serious ophthalmological condition with a potentially vision‐threatening prognosis. Early diagnosis and recognition of relapse, and the detection of persistent Acanthamoeba cysts, are essential for informing the prognosis and managing the condition. We suggest the use of in vivo confocal microscopy not only to identify the early signs of relapse after keratoplasty in patients with Acanthamoeba keratitis, but also as an additional follow‐up tool after antimicrobial crosslinking. This study shows that in vivo confocal microscopy is, in experienced hands, a quick and reliable diagnostic tool. Clin. Anat. 31:60–63, 2018. © 2017 Wiley Periodicals, Inc.